An Investigation of Volleyball Extracurriculars Coaches’ Interpersonal Communication Knowledge - Muchamad Arif Al Ardha; Chung Bing Yang; Sujarwo (Indonesia Approach Education, 2023)
Communication is very important in the training process. The trainers are not only requiring good knowledge but also good communication skills. This study aimed to determine the interpersonal communication knowledge level based on gender, age, coaching experience, and background. The research method was a quantitative approach with descriptive and comparative statistics with percentage techniques. The research samples were 27 volleyball coaches in junior high school extracurriculars (20 males and 7 females aged 36.37 ± 8.56 years old). The instrument in this study was developed to measure the coaches’ interpersonal communication knowledge. The results showed that there are significantly different in coaches’ interpersonal communication knowledge based on the age groups and coaching experience groups (p value <0.05). Coaches in the oldest group (> 40 years old) has the highest score compared with other groups (83.00 ± 6.75). Furthermore, coaches who have experience in coaching more than 20 years also achieve the highest score compared to other groups (82.20 ± 7.07). The conclusion, most coaches have good interpersonal communication knowledge. However, coaching experience could contribute the interpersonal communication knowledge better.